Bivalirudin Inhibits Periprocedural Platelet Function and Tissue Factor Expression of Human Smooth Muscle Cells. Issue 2 (29th December 2011) - Pepke, Wojciech; Eisenreich, Andreas; Jaster, Markus; Ayral, Yunus; Bobbert, Peter; Mayer, Alexander; Schultheiss, Heinz‐Peter; Rauch, Ursula
SUMMARY Aim: A major concern of stent implantation after percutaneous coronary intervention (PCI) is acute stent thrombosis. Effective inhibition of periprocedural platelet function in patients with coronary artery disease (CAD) leads to an improved outcome. In this study, we examined the periprocedural platelet reactivity after administrating bivalirudin during PCI compared to unfractionated heparin (UFH) administration. Further, the effect of bivalirudin on induced tissue factor (TF) expression in smooth muscle cells (SMC) was determined. Methods: Patients with CAD (n = 58) and double antithrombotic medication were treated intraprocedural with UFH (n = 30) or bivalirudin (n = 28). Platelet activation markers were flow cytometrically measured before and after stenting. The expression of TF in SMC was determined by real‐time PCR and Western blotting. The thrombogenicity of platelet‐derived microparticles and SMC was assessed via a TF activity assay. Results: Bivalirudin significantly diminished the agonist‐induced platelet reactivity post‐PCI. Compared to UFH treatment, the adenosine diphosphate (ADP) and thrombin receptor‐activating peptide (TRAP)‐induced thrombospondin expression post‐PCI was reduced when bivalirudin was administrated during intervention. In contrast to UFH, bivalirudin reduced the P‐selectin expression of unstimulated and ADP‐induced platelets post‐PCI. Moreover, bivalirudin inhibited the thrombin‐, but not FVIIa‐ or FVIIa/FX‐induced TF expression and pro‐coagulant TF activity of SMC. Moreover, bivalirudin reduced the TF activity of platelet‐derived microparticles postinduction with TRAP or ADP. Conclusions: Bivalirudin is better than UFH in reducing periprocedural platelet activation. Moreover, thrombin‐induced TF expression is inhibited by bivalirudin. Thus, bivalirudin seems to be a better anticoagulant during PCI than UFH.